Direitos, cidadania e educação integral nas escolas estaduais do município de Goiás (2007-2017): uma análise a partir da experiência dos sujeitos da escola - Ferreira, Paulo Sérgio Cantanheide (2019)
The thesis aims to make a critical analysis of the ten years of the integral education policy in the state schools of the city of Goiás, in interlocution with the educational policies of the state and the Federation, based on the experiences of the main subjects of school education, that is to say: students, teachers and managers. The research was developed under the qualitative and interpretative bias and used bibliographic review, documentary research, interviews and questionnaires applied to teachers and managers, and dialogue circles with students from four schools in the city of Goiás as data collection techniques. In order to analyze the relationship between the political proposition of public institutions, the other social actors involved in the field dynamics and the social practices of the subjects of the school, the thesis uses the Ball and Mainardes Policy Cycle (2011). Bourdieu’s Field Theory sought a theoretical methodological reference for the identification and understanding of the social practices of these subjects in their experiences in the school of integral education. Based on the assumption that the school of integral education finds its raison d’être in the realization of the right to education and citizenship, Arroyo’s (2012) reflection on the extension of the school day in the perspective of the right to more space and more time to a fair and dignified living was a reference to discuss the experience in Goiás. By occupying a space within the debate on educational policies in Brazil and the State of Goiás, integral education becomes an arena of dispute within the field of educational policies. By placing integral education within the correlation of political strength in the field of educational policies in Brazil, research finds, in different aspects of school education, a mismatch between the demands of the subjects of the school by right and citizenship and the offer provided by the public power.